2019
DOI: 10.5603/pjnns.a2019.0051
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of unfavourable outcome in aneurysmal subarachnoid haemorrhage

Abstract: Background. Mortality rates following aneurysmal subarachnoid haemorrhage (aSAH) have decreased due to improvements in diagnoses and the management of complications, as well as early obliteration of the aneurysms. Neurogenic pulmonary oedema (NPO) is a clinical syndrome associated with an acute increase in intracranial pressure and a release of catecholamines into the circulation. This study investigated independent predictors of unfavourable outcomes (Glasgow Outcome Scores 1, 2 or 3) in patients with aSAH. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Hypertension may cause extensive intimal hyperplasia, causing poor surgical vascular conditions to increase the difficulty of the operation and raising cerebral edema risk and secondary bleeding greatly. [ 26 ] Nastasovic et al [ 27 ] demonstrated that 46% of patients developing CVS after aSAH suffered from hypertension, which indicated that the hypertensive population was susceptible to the complications of IAs rupture, and adverse prognostic events. Furthermore, Kurtz revealed that blood glucose was positively correlated with stroke mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension may cause extensive intimal hyperplasia, causing poor surgical vascular conditions to increase the difficulty of the operation and raising cerebral edema risk and secondary bleeding greatly. [ 26 ] Nastasovic et al [ 27 ] demonstrated that 46% of patients developing CVS after aSAH suffered from hypertension, which indicated that the hypertensive population was susceptible to the complications of IAs rupture, and adverse prognostic events. Furthermore, Kurtz revealed that blood glucose was positively correlated with stroke mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] A large-scale follow-up study found that elevated blood glucose was significantly associated with mortality within 14 days after aSAH, and further confirmed the significant impact of glucose on stroke prognosis. [ 27 ] There is extensive systemic inflammatory basis for diabetics, and SAH induces intracranial hypertension and cerebral edema, affecting neuroendocrine function and insulin resistance. [ 29 ] Moreover, hyperglycemia induced the expression of p-selectin and von Willebrand factor (vWF), enhancing platelet activation and the release of intracellular oxidative stress to further aggravate the systemic inflammatory injury.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the clinical results at admission were concerned, the majority of our patients were hypertensive and tachycardic (average blood pressure 143/87 mmHg, average heart rate 83). In their recent paper, Nastasovic et al concluded that increased blood pressure and HR are associated with unfavourable outcomes in patients treated due to ruptured intracranial aneurysms [17].…”
Section: Discussionmentioning
confidence: 99%
“…flow velocity and wall shear stress) indicates a significantly lower amplitude reduction of the velocity on the neck plane in patients undergoing recanalisation [22,23]. The role of inflammation in the recanalisation process is not yet established, which is probably important bearing in mind other factors in the process of formation, progression and rupture of aneurysms [24,25].…”
Section: Discussionmentioning
confidence: 99%